Analisis Prediksi Kunjungan Pasien Dengan Metode Autoregresiive Integrated Moving Average di Rumah Sakit Ibu dan Anak Putri Surabaya - Muh Zul Azhri Rustam; Nuke Amalia; Maya Ayu Riestiyowati (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2022)
Hospitals as health care facilities are needed not only in the service sector but also in the need for recording and documenting the results of examinations, treatment, actions, and other services that have been provided to patients which are recorded in medical record documents. every patient who receives medical services at the hospital will receive a medical record document to document his medical history. The increase in patient visits is sometimes not in line with the readiness of the hospital in fulfilling the facilities and supporting service tools. The study aimed to predict the number of patient visits. The type of research used is quantitative research and the sampling technique used is total sampling by looking at the data of the last 5 years of visits in the medical record unit and the analysis used is the ARIMA method in predicting visit data. Prediction results from patient visits for the next two years tend to fluctuate quite a lot with a total of 5163 patient visits in outpatients, with a Mean Absolute Percentage Error (MAPE) value of 19% with the ARIMA model (2,1,2) which means that the prediction of visits patients can be quite accurate and reliable. So that in the future the hospital must be able to improve the facilities and quality of its services. So that the service process for visiting patients can be served effectively and efficiently.Keywords: Prediction, Patient Visit, ARIMA